55 (At Least) and not out of the Learning Game: Older Regional Students - Ellis, Bronwyn J. (Australian and International Journal of Rural Education, 2013)
This article explores older students‘ perceptions of formal, non-formal and informal learning in regional South Australia. Drawing on earlier studies as well as a continuing one, it compares: the study motivations of students aged 55 and older enrolled formally in university undergraduate programs; the learning motivations of University of the Third Age (U3A) members enrolled in various non-formal classes; and the learning of older people in other community organisations. Research focusing on these different groups of older learners was conducted via anonymous surveys. Members of a particular U3A branch, sponsored by the regional university campus at which it meets, took part some years ago in a study that investigated the importance attributed by them to continued learning and the impact on them of their U3A participation. Social as well as educational benefits were identified. In a later study investigating the reciprocal contributions of U3A and university campus, U3A members were also asked about their possible interest in undertaking formal university study, while university staff were asked how they thought these older students would fit in as enrolled undergraduate students. More recently, an online survey allowed university students of more mature years to provide an insight into their higher education experiences, both highlights and challenges, and the contributions that they were able to make to their classes from their life experience. The main focus of this paper draws on data from an ongoing survey of past, present and potential links between the university campus and local organisations with an older membership. It reveals how these age-mates of the older participants in the earlier studies regard the possibility of formal university study for themselves.The article argues that in a just, inclusive society all groups within it, including older people resident in more remote areas, should have access to lifelong learning opportunities, including both non-formal continuing education and formal higher education.